Ensaios de adubação química do feijoeiro - Vieira, Clibas; Ribeiro Gomes, Fábio (Revista Ceres, 2024)
Three bean fertilizer trials are reported using combinations of N, P, and K. The work was done in the counties of Muriaé, Viçosa, and Inhapim, in the State of Minas Gerais clayey “massapé” soils.